The Management of the Rehabilitation of Santri Drug Addicts in Islamic Boarding School - Mangun Budiyanto; Thahera Chahya Listianti (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
This study describes the management of the rehabilitation of santri drug addicts at Nurul Haromain Islamic Boarding School in Kulonprogo Yogyakarta. This research is a qualitative case study in which data were gathered through interviews, documentation and non-participant observation and validated through source triangulation. The data was then analyzed using Miles & Huberman model, involving data reduction, data display and conclusion drawing. The result shows that: 1) the management of the rehabilitation of santri drug addicts at Nurul Haromain Islamic Boarding School in Kulonprogo Yogyakarta is carried out by implementing James Stoner’s management theory i.e., planning, organizing, directing and controlling; 2) The planning stage embodies in the admission of santri drug addicts; 3) the organizing phase is manifested by the existence of organizational structure of the management of the santri rehabilitation, while the directing phase embodies in the implementation of the rehabilitation programs; 4) The controlling stage appears in regular supervision activities performed by Nurul Haromain caregiver while the supervision for the rehabilitation santri is carried out intensively by the board and room assistants.